The Characteristics and Geological Significances of Tectonic Regime Changes in Chepaizi Uplift, Junggar Basin, Western China. (23rd April 2022) - An, Bang; Wang, Weifeng; Li, Baogang; Wang, Zhaobing; Yang, Shuaijie; Sun, Yifei; Li, Xin
Abstract : Tectonic regime change refers to the process in which the two periods of tectonic movement changes and produce corresponding tectonic regime change surfaces (unconformity surfaces) and other geological responses in the process of basin development and evolution. The change of tectonic movement is the root cause of tectonic regime change. Tectonic regime changes produce different geological responses, which can be used as the signs to identify tectonic regime changes. In order to study the characteristics of tectonic regime changes of Chepaizi Uplift in Junggar Basin and the control on oil and gas migration and accumulation, four stages of tectonic regime changes were identified by using the techniques of the rock acoustic emission (AE) technology, tectonic subsidence analysis, and tectonic stratigraphic sequence analysis, which occurred at the end of Early Permian, the end of Late Triassic, the end of Jurassic, and the end of Paleogene, respectively. The main stratigraphic product of tectonic regime change is the unconformity structure. The unconformity structure has obvious stratification, including the bottom conglomerate layer, the weathered clay layer, and the semiweathered rock layer, and plays an important role in controlling oil and gas migration and accumulation. The weathered clay layer and the hydrolysis layer have a sealing and shielding effect on oil and gas; the leaching layer can become the effective reservoir; at the same time, the leaching layer can provide a channel for the lateral transportation of oil and gas.